Isolated cardiac peripheral primitive neuroectodermal tumor: A case report. Issue 1 (2nd January 2017) - Fan, Chengming; Kong, Demiao; Tan, Changming; Yang, Jinfu
ABSTRACT: Background: Peripheral primitive neuroectodermal tumor isolated in the heart, presenting as a primary cardiac tumor is considered as extremely rare. Methods: We present a 53-year-old Chinese female with a cardiac tumor which was discovered by CT. Results: A hypo-intense tumorous mass was shown extending from the left ventricle by Cardiac CT, and fused FDG positron emission tomography demonstrated no other abnormal FDG active lesions in the body. We performed a total resection surgery of the tumor subsequently and the patient recovered well and discharged from hospital 6 d after surgery. Conclusion: The pathological diagnosis was primary cardiac peripheral primitive neuroectodermal tumor. No tumor recurrence was shown by echocardiography during the 24 months follow-up visits.